Global citizenship incorporated: competing responsibilities in the education of global citizens. Issue 1 (2nd January 2017) - Hartung, Catherine
ABSTRACT: Interest in the education of young people to be 'responsible global citizens' has grown exponentially since the turn of the century, led by increasingly diverse networks of sectors, including government, community, business and philanthropy. These networks now have a significant influence on education policy and practice, indicative of wider changes in governance and processes of globalisation. Yet little of the academic literature on global citizenship education specifically examines the impact of these networks on the production of knowledge about young global citizens. This paper addresses this gap by analysing the discourses of global citizenship that underpin recent work by a youth organisation that works closely with a network of sectors in Australia. The paper finds that a particular kind of entrepreneurial global citizen is favoured, one that is simultaneously responsible for themselves, for the rights of others and for ensuring Australia's future economic prosperity.